Chest and its Esthetic and Rhetorical Connotations from the Perspective of the Qur’an - Alyabroudi, Yusra; Nassar, Dima (Dirasat: Shari’a and Law Sciences, 2021)
This study aimed at extrapolating the word chest in the Qur’an and reflecting its esthetic and rhetorical connotations, starting with presenting the linguistic and terminological meaning of chest, and then revealing meanings, connotations and correlations of the word according to its context mentioned in the Qur’an. The inductive and analytical approaches were used. The study concluded the following. First, Allah, the Almighty, has made the chest the center of human emotions and feelings. Second, the Qur’an has considered clarifying the state of chest when expanding (feeling happy) or tightness (restless) indicating that it expands with the Islam and believing in Allah and his oneness, and get tightens in the case of blasphemy of Allah. Third, the Qur’an linked between the chest word and the virtue of Taqwa (piety) indicating that the chest is the station for Taqwa in this earthly life. The repetition of this word in the Qur’an has highlighted the presence of rhetorical relations with different linguistic connotations, such as the presence of conformity in style between the swearing object and what is swore on which resulted in the presence of conformity between the word used and the intended meaning. The word chest has showed also a metaphorical and simile rhetoric that served the intended semantic purpose and provided the Qur’an an aesthetic and linguistic dimensions.